A multiple-fluids-mechanics-based model of velocity profiles in currents with submerged vegetation - Zhang, Jiao; Mi, Zhangyi; Wang, Huilin; Wang, Wen; Li, Zhanbin; Guan, Muhong (Frontiers in Marine Science, 2023)
Submerged aquatic vegetation can provide a habitat and food for marine organisms, and it has the ecological effect of purifying water by absorbing harmful substances. It therefore plays an important role in the maintenance, restoration, and improvement of marine ecosystems. Hydrodynamic problems caused by submerged vegetation have been matters of wide concern. According to the distribution of vegetation in this study, the flows can be divided into three layers in the vertical direction: uniform, mixing and logarithmic layers. This paper proposes an analytical solution model for the vertical distribution of longitudinal velocity in open-channel flows with submerged vegetation by applying a method of velocity superimposition in mixing and logarithmic layers. The velocity inside the vegetation layer is affected by drag force in the vegetation layer, which simplifies to a balance between the drag force and bed gradient. The flow at the junction between the vegetation and free surface layer is mainly controlled by the mixing layer eddies. The velocity in the mixing layer is commonly described by a hyperbolic tangent formula. The logarithmic distribution formula is applied to the free surface layer, where the logarithmic term is largely due to the turbulence scaled with the distance from the bed. The conception of wake function is introduced to modify the distribution of velocity in free surface layer. The velocity difference between the vegetation layer and the free surface layer results in the formation of a mixing layer at the top of the vegetation, the width of which is explored and improved especially for the calculation method of the width of the mixing layer. Furthermore, the expression of zone width in the mixing layer, which is divided by the flow velocity profile inflection point, is proposed. The longitudinal velocities from the theoretical model were compared to the measured velocities in the literature. We found that the theoretical solutions agreed well with the measured values in the flows, proving that the theoretical model proposed in this paper can successfully predict the vertical distribution of velocity and has more extensive adaptability.